Assessing the spin-orbit obliquity of low-mass planets in the breaking the chain formation model: a story of misalignment - Esteves, Leandro [UNESP]; Izidoro, André; Winter, Othon C [UNESP]; Bitsch, Bertram; Isella, Andrea (Oxford University Press (OUP), 2023)
The spin-orbit obliquity of a planetary system constraints its formation history. A large obliquity may either indicate a primordial misalignment between the star and its gaseous disc or reflect the effect of different mechanisms tilting planetary systems after formation. Observations and statistical analysis suggest that system of planets with sizes between 1 and 4 R has a wide range of obliquities (∼0-30°), and that single- and multiplanet transiting have statistically indistinguishable obliquity distributions. Here, we revisit the 'breaking the chains' formation model with focus in understanding the origin of spin-orbit obliquities. This model suggests that super-Earths and mini-Neptunes migrate close to their host stars via planet-disc gravitational interactions, forming chain of planets locked in mean-motion resonances. After gas-disc dispersal, about 90-99 per cent of these planetary systems experience dynamical instabilities, which spread the systems out. Using synthetic transit observations, we show that if planets are born in discs where the disc angular momentum is virtually aligned with the star's rotation spin, their final obliquity distributions peak at ∼5° or less, and the obliquity distributions of single- and multiplanet transiting systems are statistically distinct. By treating the star-disc alignment as a free-parameter, we show that the obliquity distributions of single- and multiplanet transiting systems only become statistically indistinguishable if planets are assumed to form in primordially misaligned natal discs with a tilt' distribution peaking at ≥10-20°. We discuss the origin of these misalignments in the context of star formation and potential implications of this scenario for formation models.
Keywords: planet-disc interactions; planets and satellites: dynamical evolution and stability; planets and satellites: formations and satellites; protoplanetary discs; stars: statistics